Applying biofilm hybrid system (Anaerobic-Aerobic) using coral as media on automobile wastewater treatment - Nguyen, My Linh (Journal of Technical Education Science, 2020)
In this research, automobile wastewater treatment was performed using the Hybrid system (Anaerobic-Aerobic) with coral media. The coral media is not only cheap, available but also gives high efficiency of COD and Total Kjeldahl Nitrogen removal due to its pore structure. The inlet and outlet samples were collected and analyzed daily. The research was conducted in two phases: adaptive and operative phase. During the adaptive phase, the model was operated for 2 weeks to form biofilm on the coral media. The operative phase in which divided into three periods corresponding to the organic loading rates of 0.25; 1 and 2.5 kg COD/m3d. In these stages, the efficiencies of COD and TKN removal was high and stable. Particularly, COD removal efficiencies was 74.1 ± 6.7%; 80.37 ± 12.2%; 88.1 ± 6.4%, while those of TKN were 66.59 ± 9.7%; 70.81 ± 7.7%; 79.39 ± 6.2%, corresponding to the three different organic loading rates, respectively.